Refugee, returnee, borderland: the accidental activists and Krys Lee's How I Became a North Korean. Issue 2 (3rd April 2019) - Wang, Chih-ming
ABSTRACT: Working through the entanglements of diaspora, national identification, and minority formation in the protracted aftermath of the Korean War, this article intends to take the dyadic subject of North Korean defector/refugee as an entry point for unpacking the rhetoric of freedom and salvation. Taking a cultural studies approach that regards literature as a terrain of political engagement for reconsidering the narratives of freedom in relation to the hierarchy of nationhood embedded in the protracted Cold War in Asia, I examine Krys Lee's novel How I Became a North Korean (2016), an Asian American text that weaves together the story of an Asian American returnee with those of North Korean refugees in the North Korean-China borderland. Conflating refugee and returnee, Lee's novel occasions an exploration of the ethics of co-presence that undergirded Asian American studies, to consider both the predicaments of North Korean refugees and the linkage between Asian America and Asia. Taking literature as a form of activism, this article furthermore seeks to reflect on the promise of activism by asking how the demands for the right for return may complicate the orthodox of humanitarian imagination, and render a moment for relational thinking beyond representation.